Geotextile Reinforcement Model Laboratory Test on Silt Soil - Eko Budianto,; Dina Limbong Pamuttu,; Hairulla Hairulla,; Daud Andang Pasalli, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Merauke Regency is a lowland area that has soft soil which predominates. One of the methods to overcome the subsidence in silt soil, it is necessary to strengthen it by using geotextiles. The function of the geotextile is to hold the soil surface so that there is no subsidence in the soil. This study aims to determine the carrying capacity of silt soil before and after being given geotextile reinforcement.The study used an experimental method using the addition of Geotextile (non-woven type TS600) to strengthen the carrying capacity of silt soil. The silt soil carrying capacity test was divided into several variations, namely without using geotextile reinforcement and reinforced with 1 layer, 2 layers, and 3 layers of geotextile at a depth of 10 cm, 20 cm and 30 cm.The results of research conducted in the laboratory, the use of geotextile materials to increase the carrying capacity of silt soil has increased compared to the initial conditions. Soil without using geotextiles has a greater decrease, namely at a load of 5 kN there is a settlement of 20.3 mm. By using a single layer geotextile reinforcement material at a load of 5 kN there was a decrease of 10.97 mm, while using a two layer geotextile reinforcement material at a load of 5 kN there was a decrease of 8.09 mm, and using a three layer geotextile reinforcement material with a load of 5 kN there was a decrease of 6.01 mm. It can be concluded that the use of geotextile reinforcement can reduce the settlement of silt soil.